Letter: can transient elastography and body mass index predict fibrosis regression in HBV patients on long‐term nucleoside therapy?. Issue 5 (2nd February 2017) - Barone, M.; Shahini, E.; Di Leo, A.
Abstract : Linked Content This article is linked to Seto et al paper. To view this article visithttps://doi.org/10.1111/apt.13804 .